Nursing care in the prevention of pressure injury in elderly hospitalized in the intensive care unit (Research, Society and Development, 2021)
Pressure Injury (LPP) is the result of the loss of integrity of the skin and underlying tissues that occurs when there is increased pressure under the skin, it is also related to friction and shear. Thus, the preventive actions of nursing professionals aim to prevent the emergence and progression of this problem. Therefore, this study is a bibliographic review of the integrative literature review type, which sought articles in the Electronic Scientific Library Online (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Databases databases. Nursing Data (BDENF) and elaborated a synthesis of the results found. The main nursing contributions to promote the prevention of PPL are the application of the Braden scale, change of position, reduction of skin moisture, application of fiber and hydrocolloid dressings, health education for patients and professional updating for the nurses.